Representation of foreign workers in Malaysian mainstream English newspapers - Sim, Chew Siong (2011)
Foreign workers in Malaysia are generally treated negatively by the Malaysian media. They are being represented as threats to public order by way of linking them to criminal activities in news headlines. This negative representation results in stereotyping, which in turn leads to prejudice. Manifestations of this prejudice against foreign workers include being perceived negatively by the public, and worse, being physically abused and/or mistreated by their employers—despite their positive contributions to the Malaysian economy, and accounting for, according to former Inspector-General of Police Musa Hassan, only two per cent of the national crime rate in 2006. Thus, this study aims, in some measure, to negate the power of the media to shape public opinion on the issue of foreign workers, by way of revealing the techniques used by media producers to achieve the desired reading of their media texts. This study utilises Norman Fairclough’s Critical Discourse Analysis (CDA), which states that texts function ideologically and politically in relation to their context. This study will analyse the techniques of grammar and vocabulary usage employed in news eports of foreign workers, to discover the ways in which Malaysian mainstream English newspapers are similar or dissimilar in their general stance on foreign workers. Sample news articles from the three most circulated English newspapers in Malaysia, namely the New Straits Times (including the Sunday Times), The Star (including the Sunday Star) and TheSun, from 2003 to 2010 will be analysed. In particular, sentence structures and ideologically charged words—insofar as they make readers perceive foreign workers in the manner desired by media producers—will be examined in this study. This study finds that through the passivation of sentence structure, representation of actors or doers, as well as the use of embedded ideologically charged words, and an us versus them binary opposition, the New Strait Times and The Star consistently attempt to represent foreign workers (as a whole) as a threat to public security, local employment, and public health by way of representing foreign workers as criminals, employment opportunists and as disease carriers. At the same time, these two newspapers also highlight the efficiency of the ruling authorities in dealing with the ‘threat’: the police are described as being effective in their handling of foreign workers who enter the country illegally, while the Home Ministry is represented as humane in their repeated acts of leniency towards them. In other words, the study finds that these two newspapers share the same ideological stance of building a positive image of authority figures at the expense of foreign workers.